1964
DOI: 10.1126/science.146.3644.658
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Circadian Rhythm in Cytoplasm of Acetabularia : Influence of the Nucleus

Abstract: It was shown by three different methods that in the unicellular and uninuclear green alga Acetabularia the nucleus is capable of determining the phase of the circadian rhythm of the oxygen balance in the cytoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1965
1965
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…Their research described circadian rhythms of photosynthetic output and chloroplast migration; they and other groups found that the timekeeping mechanism resided in the nucleus of the cell (33,34) . Others however have argued that the nucleus has no role in the generation of circadian rhythms as rhythms of photosynthesis persisted in enucleated cells, but that the nucleus may communicate phase information (27) .…”
Section: Acetabularia Sppmentioning
confidence: 97%
“…Their research described circadian rhythms of photosynthetic output and chloroplast migration; they and other groups found that the timekeeping mechanism resided in the nucleus of the cell (33,34) . Others however have argued that the nucleus has no role in the generation of circadian rhythms as rhythms of photosynthesis persisted in enucleated cells, but that the nucleus may communicate phase information (27) .…”
Section: Acetabularia Sppmentioning
confidence: 97%
“…However, it is unclear to what extent the nucleus contributes to circadian rhythmicity of the chloroplast in these species. On the other hand, it has been known that in the green macroalga Acetabularia, the chloroplast photosynthetic rhythm persists even in an enucleated cell (46), and the nucleus contributes only to phase determination of the rhythm (41).…”
mentioning
confidence: 99%
“…Finally, we recall the puzzling example of Acetabularia, the giant unicellular algae that shows a self-sustained circadian rhythm even if the nucleus has been "surgically" removed (Schweiger et al 1964). The dissociation of Chlamydomonas nuclear and chroloplast rhythms shown in the work here suggests that the circadian system of this microscopic algae is constructed similarly to Acetabularia.…”
Section: The Chlamydomonas Clock In Contextmentioning
confidence: 75%